"More Like a Real Human Being": Humanizing Historical Artists Through Remote Service-Learning. (December 2018) - Gasper-Hulvat, Marie
Background: In a digital age, service-learning partner organizations can expand beyond geographical locations accessible to the students. Particularly within fields digitizing archival sources, including art history, many learning outcomes achieved in traditional on-site service-learning programs can also result from remote access to staff and materials at non-local partner organizations.Purpose: This study analyzed the impact of a remote service-learning project between an upper division contemporary art history course at a regional university in Ohio and the Archives of American Art in Washington, D.C.Methodology/Approach: Over 3 consecutive years, the students used digitized visual and audio archival materials to edit transcripts of oral histories for web publication. At the conclusion of the project, the students conducted focus group interviews to analyze their perceptions of learning outcomes.Findings/Conclusions: Qualitative analysis of the interview transcripts yielded four primary themes in the data: disciplinary understanding, transferrable skill development, critical decision making, and emotional knowledge.Implications: Remote service-learning can facilitate many of the same learning outcomes as on-site experiences.